Knockdown of lncRNA AU020206 could inhibit microglia apoptosis in ischemic stroke: Inhibiting AU020206 aids ischemic stroke microglia survival - Chen, Zhihua; Hu, Wei; Wang, Jiahong; Rao, Donggen; Zhu, Jianming (Cellular and Molecular Biology, 2024)
The diagnostic biomarkers associated with ischemic stroke (IS) that may have clinical utility remain elucidated. Thus, the potential functional lncRNAs in IS were explored. The Gene Expression Omnibus database provided the transcriptome profile of IS for download. WGCNA analysis and integrated bioinformatics were used to find genes that were differentially expressed (DEGs). The Starbase database created the lncRNA-based ceRNA network. In order to investigate the molecular mechanism and involved pathways of DEGs in IS, functional enrichment analysis was carried out. Using qRT-PCR, lncRNAs identified as putative IS biomarkers were confirmed to be expressed in a permanent middle cerebral artery occlusion (MCAO) model. Using the annexin V/PI apoptosis test, the amount of apoptosis in oxygen-glucose deprivation (OGD) cells was measured. A total of 1600 common differentially expressed - protein-coding RNA (DE-pcRNAs) and 26 DE-lncRNAs were identified. The results of enrichment analysis indicate that the cytokine may be regulated by common DE-pcRNAs and are vital in the progress of IS. A lncRNAs-mediated ceRNA network including lncRNAs AU020206, Brip1os, F630028O10Rik and 9530082P21Rik was constructed. The expression of these lncRNAs was significantly increased in MCAO model. Knockdown of lncRNA AU020206 inhibited microglia apoptosis in OGD cell model. We constructed a lncRNAs-mediated ceRNA network and found that lncRNA AU020206 inhibited microglia apoptosis in OGD cell model. These findings provided further evidence for the diagnosis and a novel avenue for targeted therapy of IS.